KOMPARASI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DENGAN MODEL SIKLUS BELAJAR 7E TERHADAP HASIL BELAJAR MATEMATIKA - Nur Asrawati (Universitas Pancasakti, 2021)
This type of research is experimental research. This study aims to compare the learning outcomes of mathematics with the Think Pair Share (TPS) Learning Model and the 7E Learning Cycle Model. The population in this study were all students of class X SMK Muhammadiyah Bulukumba totaling 127 people. The sample in the study consisted of class X Kep1 which numbered 24 people, class X Kep2 which amounted to 21 people. Based on the results of descriptive statistical analysis obtained the average score of learning outcomes taught by Think Pair Share (TPS) Learning Model is 77.92 with a standard deviation of 10.660 which is categorized good while the average score of learning outcomes taught with the 7E Learning Cycle Model is 63,29 with a standard deviation of 12,170 which is categorized sufficient. Based on the results of inferential statistical analysis obtained tcount = 4.300 and ttable = 1.68. Because tcount > ttable, H0 is rejected and H1 is accepted. The results of descriptive and inferential statistical analysis showed that the mathematics learning outcomes of class I students of SMK Muhammadiyah Bulukumba were taught through the Think Pair Share (TPS) learning model higher than the mathematics learning outcomes taught by the 7E learning cycle model.